Effects of biochar on in vitro ruminal fermentation of beef cattle diets - Souza, Júlia Mara Campos de (2022)
The objective was to evaluate the effects of biochar on in vitro ruminal fermentation, methane production and diet degradation of tropical beef cattle diets high or low in forage and compare with additives that are already being used. The effects were assessed in three different studies: I) Determination of the inclusion level of biochar; II) Comparison of the effects of biochar with monensin and nitrate on ruminal fermentation and gas production; III) Comparison of the effects of biochar with monensin and nitrate on in vitro digestibility. There were five treatments for study I (0, 10, 20, 30 and 40mg/kg DM) and four treatments for Studies II and III (control, biochar (40mg/kg DM and 20mg/kg DM for high forage and high concentrate, respectively), monensin (30mg/kg DM) and nitrate (20g/kg DM)). For study I and II, data were collected and analyzed following the randomized block design and for study III were according to a latin square design. In the first study, biochar increasing levels linearly decreased IVDMO (P < 0.01), CH4 proportion (%), production (mL/g DM) and yield (mL/g OMd) (P = 0,01) in diets with high inclusion of forage. For diets with high inclusion of concentrate, treatment effects were not detected for in vitro digestibilities, but CH4 proportion, production, and yield presented a cubic effect (P < 0.02). The lowest values for CH4 were observed for 40g of biochar for diets with high forage inclusion and 20 g for diets with high inclusion of concentrate. For study II and diets with high forage inclusion the IVDOM (P = 0.05) and NH3-N concentration (P = 0,02) was affected by the additives, but CH4 yields were not affected (P = 0.14). For the diets with high concentrate inclusion, the highest total GP was verified with biochar inclusion compared to monensin (P < 0.05). Treatments did not affect in vitro digestibilities and CH4 proportion, production, as well as yield (P > 0.13), NH3-N concentration increased by biochar and nitrate compared to control and monensin (P < 0.05). For study III and diets with high forage inclusion, IVDMD was highest for monensin (P < 0.05), nitrate had greatest IVDMO (P < 0.01) and IVDCP was smallest for nitrate than the other treatments (P < 0.001). For diets with high concentrate inclusion, biochar and nitrate had the greatest IVDMD (P < 0.001). In this case, the IVDMO was higher for nitrate compared to the control, but biochar and monensin were not different to them (P > 0.05). Biochar had a greater IVDCP than control and nitrate, while monensin presented the lowest value (P < 0.02). The IVDNDF and IVDHEM were improved with biochar and nitrate addition (P < 0.001). We demonstrated that 2 and 4% of biochar inclusion level decrease in about 10 and 20% of CH4 yield when high- and low-concentrate diets were incubated, respectively. However, subsequent studies did not present significative CH4 reductions with biochar addition, regardless of type of diet.